Experimental data related to the publication "A universal framework for microscope sensorless adaptive optics: generalized aberration representations" - Hu, Q (University of Oxford, 2020)
".tiff" images collected by a two-photon microscope on a 2 µm fluorescence bead cluster slide during various different sensorless AO aberration correction processes.